A small scale polygeneration system based on compression/absorption heat pump. (5th March 2017) - Angrisani, G.; Canelli, M.; Roselli, C.; Russo, A.; Sasso, M.; Tariello, F.
Highlights: A compression/absorption heat pump is coupled with a microcogenerator. A TRNSYS model is developed to simulate the innovative system. A dynamic simulation is performed considering an office in Naples as user. Energy and environmental analyses are carried out. Different electric heat pump COP and electric grid efficiencies are considered. Abstract: In this paper a polygeneration system based on compression/absorption heat pump (CAHP) is analyzed. This innovative heat pump is contemporary activated by both thermal and electric energy, ensuring more flexibility with respect to a traditional absorption heat pump and allowing to optimize the mix of energy vectors that feeds the system. Moreover this kind of absorption system can overcome some typical disadvantages of the traditional absorption heat pump, such as the limited range in terms of operating temperatures, as well as the quite low pressure and temperature lift achievable between evaporator and condenser. The integration of a compression/absorption heat pump with cogenerator or renewable energy technologies, such as solar thermal collectors, allows to reduce the fossil fuel use. The energy performance could be optimized varying the compression ratio of the compressor. In particular increasing this parameter it is possible to reduce the heat source temperature and so to optimize the system performance that depends on the heat source temperature. Hereinafter the performance of a small scale polygeneration system based on a CAHP is analyzed considering the installation in Naples, southern Italy. A microcogenerator, fuelled by natural gas, provides both thermal and electric energy to the CAHP in order to deliver cooling energy, besides heat and electricity.